Competing With Charter Schools: Selection, Retention, and Achievement in Los Angeles Pilot Schools. (April 2020) - Kearns, Caitlin; Lauen, Douglas Lee; Fuller, Bruce
Charter schools place competitive pressure on school districts to retain students and public funding. Many districts also have moved to decentralize control of budgets and teacher hiring down to school principals, independent of competitive pressures. But almost no evaluation evidence gauges the effectiveness of charter-like schools, relative to traditional public schools. We find that autonomous pilot schools in Los Angeles enroll more low-income and Spanish-speaking students, compared with traditional schools. Pilot pupils are significantly less likely to exit the school district. But pilot pupils displayed lower test scores in mathematics and fell slightly below traditional students in English-language arts, taking into account prior performance and their propensity to enter pilot schools. We tracked 6, 732 students entering pilot high schools between 2008 and 2012, statistically matched in multiple ways with traditional peers from identical sending middle schools. We discuss the advantages of our evaluation strategy and the implications of our findings for education leaders and policy makers.